Penyuluhan tentang Pentingnya Mencantumkan Tanggal Kaduluarsa pada Kemasan Produk Kerupuk Amplang di Desa Kertasada, Sumenep - Kusuma, Rendra; Firmansyah, Raden Arief; Asih, Dessy Novitasari Laras; Andrianingsih, Very (Departemen Teknologi Pertanian Universitas Hasanuddin, 2025)
In the market, it often happens that the packaging for Amplang cracker products already has an expiration date in the form of a list of months and years, but the list of months and years is still not checked. This service aims to provide an understanding of the importance of including an expiration date on the packaging of Amplang cracker products. The method of this service uses lectures and discussions about the reasons why it is essential to include an expiration date, the expiration time of fish cracker products, the benefits of having an expiration date on the packaging for producers and consumers, and the health impacts if consumers consume expired packaged food products. It's crucial to be aware that consuming expired products can have profound health implications, underscoring the need for caution. The results of this outreach had an impact on the Amplang UD cracker UKM. Putri, from initially not checking the expiration month and year, became committed to always checking the expiration month and year of products.